An effective route for the synthesis of boron nitride micro-nano structures and the growth mechanism. Issue 5 (16th December 2014) - Pan, An; Chen, Yongjun; Li, Jianbao
Abstract : Boron nitride (BN) nanosheet-assembled microwires were successfully synthesized on the large scale and with high purity via an efficient method. Abstract : An efficient route for the large scale synthesis of boron nitride (BN) micro-nano structures called nanosheet-assembled microwires is demonstrated for the first time, by annealing amorphous boron powder with ferric chloride (FeCl3 ) at elevated temperatures in flowing ammonia. The microwires have a very well-proportioned diameter of about 2 μm, while the nanosheets have an average thickness of less than 20 nm. The nanosheets are mostly separated with a bending and crumpling morphology and nearly vertically aligned to the microwire trunk. This micro-nano structure shows strong photoluminescence (PL) emission at 357 nm. It is revealed that FeCl3 reacts with B to generate BCl3, a vital vapor for the growth of BN micro-nano structures in addition to the provision of catalyst Fe. A combination growth mechanism of vapor–liquid–solid (VLS) and vapor–solid (VS) models is proposed to be responsible for the formation of this BN micro-nano structure.